Feedback-seeking behavior in second language writing: motivational mechanisms - Papi, Mostafa; Bondarenko, Anna Vitalyevna; Wawire, Brenda; Jiang, Chen; Zhou, Shiyao (Reading & writing, 2020)
Focused on the effects of different type of feedback on learners’ written products, research on written corrective feedback (WCF) has cast second language writers as passive recipients rather than proactive agents in the feedback process. Revisiting the notion of WCF, this study introduces the notion of feedback-seeking behavior (Ashford & Cummings, 1983 ) to the field of second language writing and examines its motivational mechanisms using Dweck’s ( 1999 ) theory of mindsets and an overarching cost-value analysis framework (e.g., Ashford & Cummings, 1983 ; Anseel et al., 2015 ). Questionnaire data were collected from 128 foreign language writers from a major public university in the United States. Multiple regression and mediation analyses showed that a growth language mindset predicted the value of feedback, which, in turn, was a strong predictor of both feedback monitoring and feedback inquiry. A fixed language mindset, on the other hand, predicted the cost of feedback seeking, which, in turn, negatively predicted feedback monitoring. The findings offer new venues for second language writing research and pedagogy.